The structural and functional importance of the thalamus in migraine processes with and without aura. A literature review - Juan José Valenzuela-Fuenzalida; Alejandra Suazo-Santibañez; Marjorie Gold Semmler; Carolina Cariseo-Avila; Edmundo Santana-Machuca; Mathias Orellana-Donoso (Elsevier, 2021)
Introduction: The thalamus plays an important role in different brain functions which could include the following functions; memory, emotions, mediator in general cortical alert responses, sensorimotor control and one of the main ones which is to be a nucleus for processing sensitive information (including taste, somatosensory, visual and auditory) carrying all this towards the somatosensory cortex, which could explain the role of the thalamus in algesic processes. The exact mechanism for the generation of migraine is still a matter of research, although there is evidence that migraine pain originates in the trigeminovascular system, still it's not clear what are the morphofuncional connections of the thalamus that are implied on migraines. Therefore, the objective of this review is to know the morphofunctional alterations of the thalamus in the processes of migraine. Methods: A systematic search was carried out in the following electronic databases: MEDLINE, SCIELO, WOS, CINHAL, SCOPUS and GOOGLE SCHOLAR, using as search terms Anatomy Thalamus, Function thalamus, Migraine, Pain head, Headache pain, for which the following Boolean connectors ''AND'' ''OR'' and ''NOT'' were used. Results: After having applied the inclusion and exclusion criteria, 27 articles passed for the results analysis. 8 studies that reported the participation of nuclei of the thalamus in the process of migraine, 1 study that related the pulvinar of the thalamus with migraine; 2 articles that makes the relationship between the limbic system, thalamus and migraine; 3 articles that mention the trigeminovascular pathway and its relationship with the thalamus; 22 articles that relate the thalamocortical pathway with migraine. Conclusion: We found in this review that the functional components and connection with other structures from the thalamus to the cortex or neighboring structures are altered or disrupted, expressed as the thalamocortical pathway. We believe that new studies must be made with a thorough analysis of the structural and functional role of the thalamus with larger samples could be crucial to integrate in theoretical frameworks in order to give a better conceptualization of migraine which could translate into a better management of it.